The Tophas and the Soyots: historical and ethnographic essay - Marina V. Mongush (Novye Issledovaniâ Tuvy, 2016)
Article is devoted to small ethnic groups of the Tophas and the Soyots, who were parts of the Tuvan ethnos in the past, but later have broken away and became two independent ethnic units as a result. Their ethnic history, language, culture and a problem of identity are investigated.